Efectos de dosis y épocas de aplicación de los bioestimulantes orgánicos razormin y fitomare en el desarrollo y rendimiento de dos clones de cacao 558 y 62. - Jiménez Morejón, Elvis Iván (2013)
This research was conducted in the grounds of the farm "San Pablo", belonging to the Faculty of Agricultural Sciences, Technical University of Babahoyo, located at Km 7.5 of the way Babahoyo - Montalvo Razormin testing the organic bio-stimulants and Fitomare in cocoa clones '558 'and '62', in order to: a) evaluate the agronomic performance of the clones '558 'and '62' in the presence of organic bioestimulantes b) Determine the appropriate dose and time of application organic bioestimulantes cocoa maximize performance, and c) analyze economically the treatments tested. Treatments were the combinations of clones with organic bioestimulantes dose. Razormin doses were 0.4, 0.8 and 1.2 l / ha and Fitomare 0.4, 0.6 and 0.8 l / ha, applied at 30 and 60 days after initiation of testing. We also included a control without the presence of bio-stimulant.